PERSIAN VERSE "BOBURNOMA" (Scientific journal of the Fergana State University, 2023)
In this article, the literary relations of Uzbek and Tajik literature are considered, and attention is paid to the works of one of the representatives of the Zullisonain council - Zahiriddin Muhammad Babur. The Persian poems included in the "Buburnoma" of the king and poet - Zahiriddin Muhammad Babur testify to the relationship between these two literatures in the XV-XVI centuries and show the poet's respect for Tajik Persian literature and its representatives.Verses used and quoted in the work are discussed in the comparison of different versions, involuntary errors that occurred during its publication, its correct form in connection with the interpretation of those poems are discussed.The preparation of the correct text helps to understand the meaning, and in the subsequent editions, it is necessary to prepare the text of "Boburnoma" with deep and clear research without voluntary or involuntary distortions.